Marrow Island - Smith, Alexis M. (Houghton Mifflin Harcourt, 2016)
It has been twenty years since Lucie Bowen left the islands. Twenty years ago, the May Day Quake set loose catastrophic waves along the west coast, from Alaska to California, shattering thousands of lives. Twenty years ago, Lucie's father disappeared in an explosion at the Marrow Island oil refinery, a tragedy that destroyed the island's ecosystem and sent Lucie and her mother to the mainland to start anew. Twenty years ago, Lucie and her best friend, Katie, were just Puget Sound children, tucked up under their desks, hovering under mylar sheets, hoping to survive.